Quantitative co-expression of proteins at the single cell level--application to a multimeric FRET sensor. - Joachim Goedhart; Laura van Weeren; Merel J W Adjobo-Hermans; Ies Elzenaar; Mark A Hink; Theodorus W J Gadella (PLoS ONE, 2011)
BACKGROUND: Co-expression of proteins is generally achieved by introducing two (or more) independent plasmids into cells, each driving the expression of a different protein of interest. However, the relative expression levels may vary strongly between individual cells and cannot be controlled. Ideally, co-expression occurs at a defined ratio, which is constant among cells. This feature is of particular importance for quantitative single cell studies, especially those employing bimolecular Förster Resonance Energy Transfer (FRET) sensors. METHODOLOGY/PRINCIPAL FINDINGS: Four co-expression strategies based on co-transfection, a dual promotor plasmid, an internal ribosome entry site (IRES) and a viral 2A peptide were selected. Co-expression of two spectrally separable fluorescent proteins in single living cells was quantified. It is demonstrated that the 2A peptide strategy can be used for robust equimolar co-expression, while the IRES sequence allows expression of two proteins at a ratio of approximately 3:1. Combined 2A and IRES elements were used for the construction of a single plasmid that drives expression of three individual proteins, which generates a FRET sensor for measuring heterotrimeric G-protein activation. The plasmid drives co-expression of donor and acceptor tagged subunits, with reduced heterogeneity, and can be used to measure G-protein activation in single living cells. CONCLUSIONS/SIGNIFICANCE: Quantitative co-expression of two or more proteins can be achieved with little cell-to-cell variability. This finding enables reliable co-expression of donor and acceptor tagged proteins for FRET studies, which is of particular importance for the development of novel bimolecular sensors that can be expressed from single plasmid.